Midwives' Experiences, Education, and Support Needs Regarding Basic Newborn Resuscitation in Jordan. (June 2016) - Kassab, Manal; Alnuaimi, Karimeh; Mohammad, Khitam; Creedy, Debra; Hamadneh, Shereen
Newborns who are compromised at birth require rapid attention to stabilize their respiration attempts. Lack of knowledge regarding basic newborn resuscitation is a contributing factor to poor newborn health outcomes and increased mortality. The purpose of this study was to explore Jordanian midwives' experiences, education, and support needs to competently perform basic newborn resuscitation. Qualitative descriptive methodology was used to analyze a convenience sample of 20 midwives. A thematic approach was used to analyze the data. Participants discussed their experiences of basic newborn resuscitation including knowledge, skills, and barriers and suggested solutions to improve practice. Four themes were revealed: lack of knowledge and skills in newborn resuscitation, organizational constraints, inadequate teamwork, and educational needs. The midwives perceived that their ability to perform newborn resuscitation was hindered by lack of knowledge and skills in newborn resuscitation, organizational constraints (such as lack of equipment), and poor co-ordination and communication among team members.